CD8+ T cells promote tubule-interstitial damage in malaria-induced acute kidney injury - Douglas Esteves Teixeira; Sarah Aparecida dos Santos Alves; Alessandro Sá Pinheiro; Leandro Souza Silva; Rodrigo Pacheco Silva-Aguiar; Diogo Barros Peruchetti; Tatiana Almeida Pádua; Mariana Conceição Souza; Celso Caruso-Neves; Celso Caruso-Neves; Celso Caruso-Neves; Ana Acacia Sá Pinheiro; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionMalaria acute kidney injury (MAKI) is associated with severe malaria and correlates with poor prognosis and death of patients infected with Plasmodium falciparum. The pathogenesis of MAKI is not completely understood but some hypotheses are well recognized. Host–parasite interactions lead to mechanical obstruction, disorders in the renal microcirculation, and immune-mediated glomerular injury. We investigated the influence of CD8⁺ T cells in the pathogenesis of malaria-induced renal disease.MethodsTo assess the role of T lymphocytes in MAKI pathogenesis, we used adoptive transfer; antibody-driven CD8+ T cells depletion and treatment with FYT720.ResultsThe transference of total T cells isolated from malaria-infected donor mice into naive recipient animals reproduced kidney tubule-interstitial damage without affecting glomerular function. It was associated with increased accumulation of CD8+ T cells in the kidneys of recipient mice. The selective depletion of CD8+ T cells in infected animals resulted in protection from tubular injury, although glomerular alterations still occurred. Finally, we evaluated FTY720, an immunomodulatory drug that sequesters T cells in lymphoid organs and limits their migration, as a potential therapeutic strategy. Treatment with FTY720 prevented the development of proteinuria and the increase in the urine to creatinine ratio. Moreover, FTY720 reduced urinary γ-glutamyl transferase (γ-GT) levels, a marker of tubular injury, but did not alter plasma urea and creatinine, two markers of glomerular function.DiscussionOur results add new knowledge demonstrating that CD8+ T cells have a specific role in tubule-interstitial injury pathology during MAKI.